2022
DOI: 10.1158/1078-0432.ccr-22-1432
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of 90Y-FAPI-46 Radioligand Therapy in Patients with Advanced Sarcoma and Other Cancer Entities

Abstract: Purpose: We report efficacy and safety of 90Y-FAPI-46-RLT in patients with advanced sarcoma, pancreatic cancer (PDAC) and other cancer entities. Experimental Design: Up to four cycles of RLT were offered to patients with (a) progressive metastatic malignancy, (b) exhaustion of approved therapies, and (c) high fibroblast activation protein (FAP) expression, defined as SUVmax≥10 in more than 50% of tumor. Primary endpoint was RECIST response after RLT. Secondary endpoints included PET response (PERCIST), overall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…Since compassionate care programs differ across the world, with some countries having a liberal policy, there is reported literature of more than 100 patients that have received TRT using FAP tracers. At present, the most promising clinical data of FAP TRT was reported in advanced sarcoma, breast, thyroid, and pancreatic cancer [30,33]. In these end-stage patients, there is an unmet need for novel anti-cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since compassionate care programs differ across the world, with some countries having a liberal policy, there is reported literature of more than 100 patients that have received TRT using FAP tracers. At present, the most promising clinical data of FAP TRT was reported in advanced sarcoma, breast, thyroid, and pancreatic cancer [30,33]. In these end-stage patients, there is an unmet need for novel anti-cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Median absorbed dose for tumor lesions after the first cycle was 1.28 Gy/GBq (IQR, 0.83-1.71 Gy/GBq) per cycle for target lesions. In July 2022, the third and latest published study using [ 90 Y]Y-FAPI-46 was reported by Fendler et al (which potentially included patients of the prior study) [30]. The effectiveness (following RECIST) and safety (following CTCAE 5.0) of [ 90 Y]Y-FAPI-46 were reported in in 16, 3, 1, and 1 patient(s) with sarcoma, pancreatic, prostate, and gastric cancer.…”
Section: Clinical Datamentioning
confidence: 99%
“…Finally, in the work by Fendler et al [ 24 ], up to four cycles of [ 90 Y]DOTA-FAPi-46 RLT were administered to patients with progressive metastatic malignancy with adequate haematopoiesis and high FAP expression levels (defined as [ 68 Ga]Ga-DOTA-FAPi-46 SUV max ≥ 10 in >50% of the tumour). Twenty-one patients, including 1 patient with mCRPCa, were found to be eligible for the treatment and received 47 [ 90 Y]FAPi-DOTA-46-RLT cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Among the FAPi molecules that have been explored so far in PCa, FAPi-46 showed a longer retention time than FAPi-04 did, making it a more suitable ligand for RLT. The authors showed the feasibility of FAPi theranostics using a beta probe ([ 90 Y]DOTA-FAPi-46) [ 24 ] and a probe with a longer half-life ([ 177 Lu]Lu-FAPi-46) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation